Communication of Opinion Leader in Commodifying Contract Marriage in Siri Marriage Village in Pasuruan - Didik Hariyanto; Maulia Figo Arian Difa (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze how the communication used by opinion leaders in Kalisat village gives rise to a form of commodification of contract marriage. The method in this research is using a qualitative descriptive method. Data collection was carried out by direct field observation in which researchers went directly to the field to find data in the field and carried out in-depth interview techniques that were carried out freely. The results of this study are, in the commodification process of this contract marriage there is a form of communication in which this communication is carried out face to face or face to face, namely a communication process carried out by the communicator to a communicant which is carried out directly without any help or intermediary of a media. The communication technique used by opinion leaders to invite and convince prospective brides and grooms, both men and women, is to use persuasive communication techniques. Where opinion leaders try to persuade and promise a number of advantages if they want to follow this practice, this is in accordance with the basic principles of commodification theory which changes something that initially only has use value and then turns it into something that can be sold and has a selling value in the market.